Konsep, prinsip, dan prosedur pengembangan modul sebagai bahan ajar - Abdul Gafur (Universitas Negeri Yogyakarta, 2010)
This article discusses the concepts, principles, and procedures indeveloping instructional module as a unit of instruction. It best suited forindividualized learning. A module is an instructional package completed with theobjectives, lesson content, strategies, exercises, feedback, and tests.To deliver instructional message, there are two important principles thatcan be used in developing instructional module. First is instructional messagedesign (readiness and motivation, attention directing device, student’s activeparticipation, repetition, and feedback), and the second is the contextual teachingand learning (relating, experiencing, applying, cooperating, and transferring).Those principles should be used in all of the components of instructionalstrategies (pre-instructional activities, presenting instructional material, learningguidance, eliciting performance, feedback, testing, and follow up activities(enrichment and remedial).The steps in developing modular instruction begin with writing theobjectives, selecting instructional materials, determining instructional strategies,selecting media, developing instrument and evaluation procedures, and the last iswriting the reference.Key words: Modular instruction, instructional message design, contextualteaching and learning, instructional strategy